The Management of Cyanotic Spells in Children with Oesophageal Atresia - Bergeron, Mathieu; Cohen, Aliza P.; Cotton, Robin T. (Frontiers in Pediatrics, 2017)
Cyanotic spells, also known as blue spells, dying spells, or apparent life-threatening events (ALTEs), refer to a bluish tone visible in the mucosal membranes and skin caused by an oxygen decrease in the peripheral circulation. Although this decrease may be transient and benign, it may also be indicative of a severe underlying problem that requires immediate intervention. Children with oesophageal atresia (OA) are at risk for a number of coexisting conditions that may trigger cyanotic spells. This current article will focus on the management of cyanotic spells both in children with innominate artery compression and those with tracheomalacia